THE PORIFERASTA COMPOUND-5,22E,25-TRIEN-3-Oβ FROM Clerodendrum paniculatum LEAF AS INDUCER AGENT OF SYSTEMIC RESISTANCE ON RED CHILLI PLANT Capsicum annuum L FROM CUCUMBER MOSAIC VIRUS (CMV) - Weny Musa; Hersanti Hersanti; Achmad Zainuddin; Roekmi-ati Tjokronegoro (Indonesian Journal of Chemistry, 2009)
The poriferasta-5.22E.25-trien-3β-ol compound of leaves of this plant Clerodendrum paniculatum has activity as an inducer agent of plant systemic resistance of red plant toward Cucumber Mosaic Viruses (CMV), the inhibition activity compound shows 82% inhibition activity at 300 ppm. The structure of these compound were determined on the basis of spectroscopic data including UV, IR, 1H-NMR, 13C-NMR and 2D-NMR